Efficacy and Safety of Testosterone Treatment in Male Hypogonadism: a Systematic Review - Ekvan Danang Setya Pramudito; Fergie Marie Joe Grizella Runtu; Amalia Dwi Mulyani; Ardy Wildan (‎ InaJEMD - Indonesian Journal of Endocrinology Metabolic and Diabetes, 2025)
Male hypogonadism may occur because of either congenital conditions or dysfunction that arises along the hypothalamic-pituitary-gonadal axis. As part of the lifelong management of male hypogonadism, testosterone replacement therapy (TRT) has been the most important therapy, although its effectiveness and safety are subject to controversy. This systematic review was undertaken to investigate the effectiveness and safety of TRT in men with hypogonadism. Searches were conducted in the literature through MEDLINE, CENTRAL, and ScienceDirect. The inclusion criteria were restricted to RCTs reported within five years. Out of 2,471 published articles, 16 were found eligible for analysis. Results showed that TRT is effective in raising serum testosterone levels in male with hypogonadism no matter the mode of administration, whether injected, oral or topical as in gels. In addition, TRT has improved body composition by decreasing fat and lean muscle mass. An increase in PSA commonly occurs in most patients, yet no research proves that TRT increases the development of prostate cancer and cardiovascular disease. Most commonly, the adverse effects are arrhythmias and increase in blood pressure, especially among those who undergo oral TRT. Amelioration of different symptoms such as erectile dysfunction, decreased libido, and fatigue in patients with hypogonadism was also achieved by TRT. Overall, it can be concluded that, TRT is generally safe and effective but requires close monitoring, but also one where monitoring should regularly be performed because of possible side effects, more research is needed.